An innovative approach to construct photodegradation curves for TiO2 incorporated latex coatings via probing localized degradation. (November 2016) - Pang, Yongyan; Huang, Pengke; Zhang, Lihua
Abstract: The main objective of this study was to establish a new approach to construct local photodegradation curves for TiO2 incorporated latex coatings via innovatively probing polymer photodegradation in the vicinity of nanoparticle agglomerates using laser scanning confocal microscope (LSCM) under a wet and a dry conditions. First, nanoparticle dispersion in surface/subsurface of latex coatings was investigated with LSCM. Second, 2D LSCM images were used to show how nanoparticles were gradually revealed with UV exposure. Third, 3D and ortho LSCM images were applied to illustrate how polymer surface was gradually decreased and how the polymer/nanoparticle interface regions were gradually degraded. The ortho images were also used to calculate the relative vertical height change in polymer matrix and in interface regions referred to the front of nanoparticle agglomerates. Finally, local photodegradation curves in the polymer matrix and in the interface regions were obtained under the wet and dry conditions by plotting the relative changes in height as a function of the UV exposure time. By comparison of the local photodegradation curves in different stages, at different locations and under different exposure conditions, it was found that under UV radiation, after the exposure of nanoparticles onto polymer surface, the photocatalytic effect of nanoparticles could significantly affect the photodegradation of the interface of filled coatings, which would result in severely inhomogeneous photodegradation, especially under the wet condition.